Inovasi Pengolahan Pangan Lokal Alpukat Berbasis Formula Modisco sebagai PMT Bergizi Tinggi pada Kelompok Wanita Tani Desa Lerep Kabupaten Semarang - Sugeng Maryanto; Afiatna, Puji; Devi, Chindya Paramitha; Novia Eka Rahmawati; Siska Dea Novitasari; Vanes Ufi Safarah (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
Lerep Village, located in West Ungaran District, Semarang Regency, has significant agricultural potential, particularly for avocado commodities that began harvesting in 2024. However, the utilization of the harvest is still limited to fresh fruit sales, making it vulnerable to post-harvest damage and price fluctuations. This community service program aims to empower the Rejomulyo Women Farmers Group (KWT) in Lerep Village through the innovation of processing avocados into nutrient-dense food products based on the MODISCO (Modified Dietetic Skimmed Milk and Coconut Oil) formula as supplementary feeding (PMT) to support community nutrition improvement. The program also seeks to initiate entrepreneurship among KWT members through the production of avocado-based ice cream. The implementation methods included socialization, training on formulation and processing, application of appropriate technology, production assistance, and quality evaluation. The results showed increased knowledge and skills among KWT members in avocado processing technology, the establishment of an internal production team, and the successful production of high-nutrition MODISCO–avocado ice cream with labeled packaging. Commercialization has also begun through sales to local residents and participation in the village’s cultural and arts festival. This program supports local food security, women’s empowerment, and stunting prevention efforts through the diversification of functional food products.   ABSTRAK Desa Lerep di Kecamatan Ungaran Barat, Kabupaten Semarang, memiliki potensi pertanian yang besar terutama pada komoditas alpukat yang mulai panen sejak 2024. Namun, pemanfaatan hasil panen masih terbatas pada penjualan segar sehingga rentan terhadap kerusakan pascapanen dan fluktuasi harga. Kegiatan pengabdian ini bertujuan meningkatkan pemberdayaan Kelompok Wanita Tani (KWT) Rejomulyo Desa Lerep melalui inovasi pengolahan alpukat menjadi produk pangan bergizi tinggi berbasis formula MODISCO (Modified Dietetic Skimmed Milk and Coconut Oil) sebagai Pemberian Makanan Tambahan (PMT) untuk mendukung perbaikan gizi masyarakat, serta menginisiasi KWT dalam berwirausaha produk es krim. Metode pelaksanaan meliputi sosialisasi, pelatihan formulasi dan pengolahan produk, penerapan teknologi tepat guna, pendampingan produksi, serta evaluasi mutu. Hasil kegiatan menunjukkan peningkatan pengetahuan dan keterampilan KWT dalam teknologi pengolahan alpukat, terbentuknya tim produksi internal, serta dihasilkannya produk es krim modisco-alpukat bergizi tinggi dalam kemasan berlabel, serta telah dilakukan komersialisasi dengan menjual es krim pada warga sekitas dan tampil dalam kegiatan gelar budaya dan seni Desa Lerep. Program ini mendukung ketahanan pangan lokal, pemberdayaan perempuan, dan upaya pencegahan stunting melalui diversifikasi pangan fungsional.